Role of Teachers in Digital Instructional Era - Fitria, Happy; Suminah, Suminah (Journal of Social Work and Science Education, 2020)
The birth of a digital knowledge-based community brought major changes in everything. The role of teachers in learning in the digital age requires the expertise of teachers to implement appropriate solutions to various problems and adapt to changing environments. This change requires a new orientation in education that emphasizes creativity, initiative, innovation, communication and cooperation. In the digital age, teachers are needed to be able to keep up with the times, can play various roles as change bearers, learning consultants; who have a high sense of humanity and morals, and social sensitivity, and are rational and honest-minded, so that they are able to work well in a dynamic educational environment. This article discusses the role of teachers in the digital age in learning that is thought to influence vision, responsibility, social sensitivity, logical ability and teacher honesty. All of this boils down to the role of teachers in the digital age as agents of change and learning consultants. The teacher becomes a bridge of revolution by making himself as motivator which moves students to accessible learning resources.